Diagnostic comparison between cord blood and filter paper for the screening of congenital hypothyroidism. Issue 1 (3rd December 2021) - Alameer, Seham; Althobaiti, Eman; Alshaikh, Saud; Turjoman, Meshari; Badriq, Feras; AlSofyani, Abeer; Mujalled, Mohammed; Borai, Anwar
Abstract: Background: Cord‐blood and heel‐prick TSH levels are essential in diagnosing and preventing the serious complications of congenital hypothyroidism, which mainly include intellectual disability. The study aimed to compare between cord‐blood and heel‐prick TSH sensitivity and specificity in detecting congenital hypothyroidism (CH) among newborn screened babies. Method: The study included 21, 012 newborn screened babies for congenital hypothyroidism starting from September 2013 until March 2019. Both cord‐blood and heel‐prick TSH were collected from each newborn. Heel prick and cord‐blood TSH cutoff values of >21 μU/ml and >30 mIU/L respectively were considered positive. Results: Out of the total screened newborns, 12 were confirmed for having primary congenital hypothyroidism. Nine cases were positive for cord‐blood TSH (Sensitivity 75%, specificity 99.9%, and a recall rate of 0.004%), while 139 cases were positive for heel‐prick blood TSH (Sensitivity of 100%, specificity of 99.3%, and a recall rate of 0.60%). Conclusion: For the screening of CH, heel prick is considered a superior method, but cord blood remains a practical option due to its cost‐effectiveness, immediate action, and lower recall rate. Therefore, whenever recall is difficult and/or early discharge is the practice, cord blood is an alternative method to heel prick but not with cases of prematurity. Abstract : Cord blood and heel prick TSH levels are essential in diagnosing and preventing congenital hypothyroidism (CH). Out of the total screened newborn 12 were confirmed for having primary congenital hypothyroidism. 10 cases were positive for cord blood TSH (Sensitivity 75%, specificity 99.9%, and a recall rate of 0, 004%) while 139 cases were positive for heel prick blood TSH (Sensitivity 100%, specificity 99.3%, and a recall rate of 0.60%). Cord blood is an alternative method to heel‐prick but not with cases of prematurity.